Orthognathic Surgery as Class III Skeletal Treatment in a 31-Year-Old Female with Mandible Prognathism: A Case Report - Sadputranto, Seto Adiantoro; Setiawan, Arlette Suzy; Maskoen, Ani Melani; Laviana, Avi; Sjamsudin, Endang (European Journal of Dentistry, 2023)
Mandible prognathism or malocclusion skeletal class III is facial deformities. These deformities can affect orofacial function, such as mastication, speech, and function of the temporomandibular joint. Besides the physical effects of these deformities, the psychosocial impact on the individual is often essential, and such deformities can affect the quality of life and self-confidence. Orthognathic surgery is designed to correct these deformities because these deformities could not have been corrected by only orthodontic treatment. Therefore, at Hasan Sadikin General Hospital, orthognathic surgery is the treatment choice for mandibular prognathism or malocclusion skeletal class III. In this case report, we present a 31-year-old female with mandibular prognathism, difficulty in closing her mouth and anterior open bite. Surgery was performed by Le Fort 1 osteotomy for advancing maxilla and bilateral sagittal split osteotomy for setback mandible. Two weeks after surgery, patient came back to the orthodontic department for occlusion treatment.
Keywords: mandible prognathism; orthognathic surgery; malocclusion skeletal class III